Integrated Genome and Transcriptome Sequencing to Solve a Neuromuscular Puzzle: Miyoshi Muscular Dystrophy and Early Onset Primary Dystonia in Siblings of the Same Family - Zhu, Feng; Zhang, Fengxiao; Hu, Lizhi; Liu, Haowen; Li, Yahua (Frontiers in Genetics, 2021)
Background Neuromuscular disorders (NMD), many of which are hereditary, affect muscular function. Due to advances in high-throughput sequencing technologies, the diagnosis of hereditary NMDs has dramatically improved in recent years. Methods and Results In this study, we report an family with two siblings exhibiting two different NMD, Miyoshi muscular dystrophy (MMD) and early onset primary dystonia (EOPD). Whole exome sequencing (WES) identified a novel monoallelic frameshift deletion mutation (dysferlin: c.4404delC/p.I1469Sfs∗17) in the Dysferlin gene in the index patient who suffered from MMD. This deletion was inherited from his unaffected father and was carried by his younger sister with EOPD. However, immunostaining staining revealed an absence of dysferlin expression in the proband’s muscle tissue and thus suggested the presence of the second underlying mutant allele in dysferlin. Using integrated RNA sequencing (RNA-seq) and whole genome sequencing (WGS) of muscle tissue, a novel deep intronic mutation in dysferlin (dysferlin: c.5341-415A > G) was discovered in the index patient. This mutation caused aberrant mRNA splicing and inclusion of an additional pseudoexon (PE) which we termed PE48.1. This PE was inherited from his unaffected mother. PE48.1 inclusion altered the Dysferlin sequence, causing premature termination of translation. Conclusion Using integrated genome and transcriptome sequencing, we discovered hereditary MMD and EOPD affecting two siblings of same family. Our results added further weight to the combined use of RNA-seq and WGS as an important method for detection of deep intronic gene mutations, and suggest that integrated sequencing assays are an effective strategy for the diagnosis of hereditary NMDs.